Manajemen BAZNAS Dalam Distribusi Zakat Pada Program Rumah Layak Huni BAZNAS Di Kabupaten Langkat - Surya, Surya; Muniruddin, Muniruddin (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to determine the management of zakat distribution by the National Zakat Agency (BAZNAS) of North Sumatra Province through the BAZNAS Decent Housing (RLHB) program for underprivileged communities in Langkat Regency. Data collection from this qualitative study was through observation, interviews, and documentation. The results show that the management of zakat distribution by BAZNAS North Sumatra has been running according to the principles of transparency and accountability. Although there are still obstacles in the aspect of budget limitations and mustahik data collection which are overcome by using the Sustainable Livelihoods Framework (SLF) Theory to comprehensively identify the conditions of prospective mustahik. The recommendations are in the form of increasing coordination with local governments and strengthening the mustahik data collection system to optimize zakat distribution.